ANALISIS POLA PEMBIAYAAN PRODUK TURUNAN PALA SEBAGAI KOMODITI PANGAN UNGGULANDI PROVINSI SULAWESI UTARA - Caroline B.D. Pakasi; Ellen ., Tangkere (Sam Ratulangi University, 2017)
Analysis of the financing pattern of nutmeg derivative products as featured food commodities in North Sulawesi province is important because Pala as a unique commodity that has economic value of an important food in the area. Nutmeg plant parts that have economic value is part of the fruit is composed of 83.3 per cent of the fruit flesh; 3.22 percent mace; Shell beans 3.94 percent, and 9.54 percent of the meat seeds. The specific objective of this study is to identify the type and Value Added Food Products Derived Pala as seed and analyze the pattern of financing products derived nutmeg as featured food commodities in North Sulawesi Province. This research was conducted in the central areas of the North Sulawesi province Pala in Sitaro Islands Regency (Sitaro). Identification will be conducted on several types of meat derived products will be analyzed nutmeg and nutmeg as a development financing patterns featured food commodities in North Sulawesi Province. The results showed that there are three types of food products derived nutmeg seed as the Dodo Nutmeg, Nutmeg Butter and Syrup Pala. Household businesses are identified financed by Four Types of Financing Pattern. They are the Financing Pattern of Government, Financing Pattern of Banking through Bank Indonesia, Pattern Loan Financing fellow entrepreneurs who have capital and Financing Pattern Alone. Featured Product Development Food must be improved by facilitating the entrepreneurs to get venture capital to increase the capacity of the Financing Patterns provided, or by credit facilities from banks.